PERCEPTIONS AND EXPERIENCES OF ELDERLY BENEFICIARIES REGARDING THE IMPACT OF THE SAGE PROGRAM ON THEIR NUTRITIONAL WELL-BEING IN NAZIGO SUBCOUNTY KAYUNGA DISTRICT. A CROSS-SECTIONAL STUDY. - Kyarisiima, Bella; Kungu , Joseph; Okello, Elizabeth; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2024)
Background The causes of food insecurity in Uganda are multifaceted, including climate vulnerability, political instability, gender inequality, rising conflict, increasing food prices, and livestock diseases among others. The study aims to assess the perceptions and experiences of elderly beneficiaries regarding the impact of the SAGE program on their nutritional well-being. Methodology A cross-sectional descriptive study design was employed, involving 120 elderly participants who were beneficiaries of the SAGE program. Data were collected using structured interviews and a pre-tested questionnaire covering socio-demographic characteristics, food security status (assessed via HFIAS), and perceptions of the SAGE program. Descriptive and inferential statistics, including logistic regression analysis, were utilized to identify factors associated with food insecurity. Results The majority, 58.3% (n=70), had no formal education, 33.3% (n=40) had completed primary education, and only 8.3% (n=10) had attained secondary education, 62.5% (n=75) indicated that the grant had no effect, 23.3% (n=28) of respondents reported that the grant had either negatively or very negatively impacted their ability to purchase food. 14.2% (n=17) felt that the grant had positively or very positively affected their ability to buy food. Over 20.0% (n=24) of respondents noted a slight improvement, while only 5.8% (n=7) reported significant improvement in their nutritional status. Conversely, 54.2% (n=65) of respondents indicated no change in their nutritional well-being, and 20.0% (n=24) experienced a slight decline. Conclusion The SAGE program, while providing some financial assistance, has a limited impact on food security and nutritional well-being. Recommendations Providing educational and awareness programs for the elderly on nutrition, health, and financial management could empower them to make better decisions and improve their food security.